Do the new canons on the consecrated state require the intention of renewing a temporary commitment on its expiration? - Gallen, Joseph F. (Review for religious, 1978)
Die neuen Canones zum geweihten Stand verlangen nicht die Intention, ein zeitliches Gelübde nach seinem Ablauf zu erneuern. (Antwort auf eine Anfrage)